2018
DOI: 10.2967/jnumed.118.221150
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-Binding PSMA Ligands: Implications for Expanding the Therapeutic Window

Abstract: Despite significant gains in the treatment of metastatic castrationresistant prostate cancer by radioligands targeting prostate-specific membrane antigen (PSMA), 30% of patients never respond to therapy. One possible explanation is insufficient dose delivery to the tumor because of suboptimal pharmacokinetics. We have recently described RPS-063, a trifunctional ligand targeting PSMA with high uptake in LNCaP xenograft tumors but also in kidneys. We aimed to use structural modifications to increase the tumor-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 24 publications
3
73
0
Order By: Relevance
“…The IC 50 of RPS-074 was determined to be 12.0 6 3.4 nM, a value consistent with the reported PSMA affinities of structurally analogous trifunctional ligands such as RPS-072 (16).…”
Section: In Vitro Evaluationsupporting
confidence: 82%
See 2 more Smart Citations
“…The IC 50 of RPS-074 was determined to be 12.0 6 3.4 nM, a value consistent with the reported PSMA affinities of structurally analogous trifunctional ligands such as RPS-072 (16).…”
Section: In Vitro Evaluationsupporting
confidence: 82%
“…With this in mind, we have focused our efforts on maximizing the therapeutic window of these powerful radiopharmaceuticals. Our choice of RPS-074 for preclinical therapy studies follows the identification of the recently reported analog RPS-072 (16), which showed dramatically reduced kidney uptake and substantially increased and prolonged tumor uptake relative to several novel PSMA-targeting ligands, including PSMA-617, RPS-063 (23), CTT1403 (24), PSMA-Alb-02 (19), and PSMA-Alb-56 (25). Although the DOTA-containing RPS-072 also chelates 225 Ac 31 , radiolabeling yield was only 49%, and the 225 Ac-DOTA complex has been found to have suboptimal in vivo stability (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum albumin ( 43 ) functions as a significant regulator of plasma oncotic pressure and a transporter of ligands ( 44 46 ). It has a half-life in the body of about 20 days and decreases by 10–15% after 50 years of age ( 47 ).…”
Section: Human Serum Albuminmentioning
confidence: 99%
“…The activity concentration in blood 1 h pi was as high as 32 ± 4% ID/g and decreased only 3.5-fold at 24 h pi. Such extension would not be possible for the relatively small ABD-RM26 conjugate (7 kDa) without interaction with albumin in blood circulation [ 35 , 36 , 37 ]. High activity concentration in blood contributed to elevated activity uptake in non-targeted organs (see Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%